FEATURES OF PROFESSIONAL TRAINING OF MASTERS PEDAGOGICAL PROFILE - O.H. Korkishko; S.A. Sayapina (Academy of Cognitive and Natural Sciences, 2008)
The problem of high-quality preparation of a future teacher in the conditions of introduction of the Bologn system, in the educational process of high school is examined in the article. The of educational-upbringing work in the preparation o f students applying for Master's olegree to professional activity is discovered in the article.